Unravelling the Threads: Bibliometric Exploration of Islamic Family Law Research in Southeast Asia (2004-2024) - Agha, Khuluq Dhaifallah Muhammad; Mahmoud Ibrahim El Nafad; Sutrisno Hadi (Nurani, 2024)
This study takes a closer look at how research on Islamic family law in Southeast Asia has evolved between 2004 and 2024, with the goal of understanding how this field has grown and where it might still fall short. Using bibliometric analysis and tools like Vosviewer to map out research trends, the study shows that countries like Indonesia, Malaysia, and Singapore have been particularly active in producing studies on Islamic family law. In fact, these nations are leading the way, contributing significantly to the global conversation. However, despite this impressive research activity—based on an analysis of 1,091 documents from Scopus—many of the most pressing issues, such as marriage, divorce, and inheritance, still lack comprehensive solutions. The research so far has provided valuable insights, but it hasn’t fully addressed the complexities that Muslim families face in these areas. Looking forward, the study suggests that future research needs to dig deeper into the dynamics of Islamic family law and focus on finding practical solutions to these ongoing challenges. By doing so, scholars can create a more responsive legal framework that better meets the real-life needs of Muslim families in Southeast Asia, ensuring that research has a meaningful impact on everyday family life.